DIPG-43. PEDIATRIC NON-PONTINE DIFFUSE MIDLINE GLIOMA H3K27M MUTANT: A MONOINSTITUTIONAL EXPERIENCE. Issue 2 (22nd June 2018) - Schiavello, Elisabetta; Biassoni, Veronica; Pecori, Emilia; Diletto, Barbara; Antonelli, Manila; Modena, Piergiorgio; Gandola, Lorenza; Massimino, Maura
Abstract: BACKGROUND: The new entity "diffuse-midline-glioma H3K27M-mutant" has been specified in the 2016 WHO revision. Recent studies have shown this tumor subtype had aggressive clinical behavior and dismal prognosis, sharing the same outcome as DIPG. No prospective studies have been so far published. METHODS: We report our experience since 2016 in treating patients with radiotherapy and Nimotuzumab/Vinorelbine chemotherapy, as already published for DIPG's patients (DOI10.1007/s11060-014-1428-z). All patients provided written informed consent for treatment. RESULTS: We treated 6 patients: 5/6 females, median age at diagnosis 9 years, median onset of symptoms 2 months, 3 thalamic, 2 ponto-cerebellar, 1 with two different lesions (brain-stem/cerebellar), no one with spinal cord dissemination. 3/6 were biopsied, the others received partial resection, in all cases a central review of diagnosis was performed: 5 patients had diffuse-midline-glioma H3K27mutated and 1 anaplastic-astrocitoma with loss of trimethylation (ongoing sequencing for mutation). One patient is on treatment two months after diagnosis. Five patients were evaluable for response: median time to progression was 9 months: range 7–12. Three out of 5 died for PD, 1 for an acute event of unknown origin, 1 is alive at 12 months SD after reirradiation. Median observation time from diagnosis was 11 months (range 2–12). CONCLUSIONS: The phenotypically/molecularly defined setting and severe outcome of this orphan population provides a rationale for therapies directed against the effects of the H3K27 mutations that are by now not yet proved and suggests inclusion of these entities in DIPG treatment registry and protocols.